Pengaruh Dana Perimbangan dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah dengan Pendapatan Asli Daerah sebagai Variabel Intervening - Saidah, Fadilatul; Maslichah, Maslichah; Mawardi, M. Cholid (Universitas Islam Malang, 2024)
This research aims to determine the effect of balancing funds and capital expenditure on regional government financial performance through local original income (empirical study of city/district regional governments in East Java province). The variables used in this research are balancing funds and capital expenditure (dependent variable). The independent variable is the financial performance of the regional government, while the intervening variable is local original income. The results of this research show that the Balancing Fund variable is on Regional Government Financial Performance, the Capital Expenditure variable is on Regional Government Financial Performance, the Balancing Fund is on Regional Original Income, Capital Expenditure is on Regional Original Income and Original Regional Income is on Regional Government Financial Performance.Keywords: Balancing funds, capital expenditures, regional government financial performance and regional original income